Analysis of alternative national development pathways for the cattle system in Ethiopia: Linked economic and animal systems (LEAS) model - Aragie, Emerta A.; Thurlow, James (Commonwealth Scientific and Industrial Research Organisation, 2024)
The livestock sector is undergoing rapid changes, and governments are designing sector development plans to account for this transition. However, the fundamental assumptions behind the medium- to long-term growth strategies of the sector should be looked at from the perspective of the dynamics in the domestic and global economy, and uncertainties around the driving forces of the transition.This study used the case of Ethiopia to provide a scenario-based analysis of alternative national development trajectories, focusing on the prospects of growth performance, urbanisation, and their potential implications on the cattle system within the country.We employed a newly developed linked economic and animal systems (LEAS) model where the livestock, economy-wide, and microsimulation subsystems are linked either way through flows of information.Our findings suggested that demand for animal-source food (ASF) is highly dependent on economic-demographic changes and that income growth is the primary driver of overall livestock-system expansion. Additionally, urbanisation shifts the outputs of the livestock systems towards processed ASF products.The analysis showed that livestock development plans should reflect the economic reality and potential risks facing the economic system. Herd offtake and livestock sector output vary considerably with assumptions about future growth and urbanisation trajectories.In addition to relevant findings about the implications of the interplays between the economic and demographic variables, the study generated insights into the role of integrating economy-wide and livestock-system models to provide a risk-based approach to the prospects of the livestock sector.